Investigating the Effects of Cyberculture on the Academic and Social Life of Resident Students - KATCHE Kadjo, Alfred Apollinaire (My University, 2020)
The Internet involvement in today’s social strata infuses new impulses in manners of doing, thinking, acting, etc. It catalyzes to welcome a new culture, known as cyberculture. Over the last decades it has become a common practice that is accessible and available to everyone. Empirical evidences raised concerns about this constant global trend motion and its influence on users’ behaviour both in cyberspace and real life. In the academic domain, the Internet changes students’ reality. However, despite the intrusion of the Internet in academic surroundings and the heavy use in students’ daily life, it barely exists studies that measure the effects of cyberculture in the Algerian context. It is therefore uncertain the extent to which it imbeds in our educational system and the practices derived from the Internet. We attempted to investigate how cyberculture affects the academic and social life of foreign resident students. The sample was a random selection of 35 foreign students at Benyahia Belkacem residence of Mostaganem, issued from different branches of study. We used a questionnaire to collect and analyze data through descriptive statistics. We found that our sample use of the Internet as main source of learning and their online behaviour, weight both positive and negative effects on their academic and social life.
A case study of foreign resident students at Benyahia Belkacem university residence in Mostaganem
Keywords: Cyberculture; Cyberspace; Foreign students’ behaviour